2007
DOI: 10.1095/biolreprod.106.054791
|View full text |Cite
|
Sign up to set email alerts
|

Decidual Stromal Cell Response to Paracrine Signals from the Trophoblast: Amplification of Immune and Angiogenic Modulators1

Abstract: During the invasive phase of implantation, trophoblasts and maternal decidual stromal cells secrete products that regulate trophoblast differentiation and migration into the maternal endometrium. Paracrine interactions between the extravillous trophoblast and the maternal decidua are important for successful embryonic implantation, including establishing the placental vasculature, anchoring the placenta to the uterine wall, and promoting the immunoacceptance of the fetal allograph. To our knowledge, global cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(214 citation statements)
references
References 62 publications
6
200
0
2
Order By: Relevance
“…More recently, gene expression profiling of hESCs has shown that levels of many hESC mRNAs are modulated in response to trophoblast-conditioned medium (23) or after coculture with firsttrimester trophoblast explants (34), further corroborating the concept of embryo-mediated modulation of endometrial cell gene expression. Here, we have demonstrated that in vitro, the human embryo induces changes in hESC RacGAP1 expression levels.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…More recently, gene expression profiling of hESCs has shown that levels of many hESC mRNAs are modulated in response to trophoblast-conditioned medium (23) or after coculture with firsttrimester trophoblast explants (34), further corroborating the concept of embryo-mediated modulation of endometrial cell gene expression. Here, we have demonstrated that in vitro, the human embryo induces changes in hESC RacGAP1 expression levels.…”
Section: Discussionmentioning
confidence: 79%
“…The activity of Rac1 and other Rho GTPases can be regulated by guanine nucleotide exchange factors and dissociation inhibitors, which control the exchange of GDP for GTP, and by GTPase-activating proteins (GAPs) that promote GTP hydrolysis. Previous microarray data demonstrated that Rac-GAP1 (also known as MgcRacGAP) is down-regulated in hESCs after exposure to trophoblast-conditioned medium (23). We analyzed RacGAP1 expression in hESCs to determine whether the embryo-induced increase in hESC Rac1 activity that we observed in vitro resulted from localized inhibition or down-regulation of RacGAP1, which, in other cell types, inactivates Rac1 (24).…”
Section: Levels Of Hesc Racgap1 Are Decreased Locally In Response To Thementioning
confidence: 91%
“…Studies using stromal cells of the human endometrium decidualized with progesterone and treated with the conditioned media from trophoblasts indicated that human trophoblast signals the decidua, which in turn amplifies conceptus signals, especially related to immune modulation and angiogenesis, resulting in an enriched cytokine environment (Hess et al 2007). Immune response is one of the most highly represented gene ontology categories of upregulated genes in response to trophoblast-secreted products in decidual stromal cells.…”
Section: Some New Insights On Pg Synthesis During Early Pregnancy In mentioning
confidence: 99%
“…Although the IFN-τ are unique to the Ruminantia, a sub-order within the much larger Artiodactyla order, there are hints from transcriptional profiling experiments that a partial interferon-response occurs in humans and mice as the trophoblast makes intimate contact with the maternal endometrium and induces the formation of a deciduum, in which stromal fibroblast proliferate and form an edematous structure adjacent to the site of implantation (37)(38)(39). This response does not involve a full-blown up-regulation of many interferon-stimulated genes (ISGs), as noted in the sheep endometrium during early pregnancy (12,13,40), but is instead more limited.…”
Section: Type 1 Ifn and Pregnancymentioning
confidence: 99%